2010
DOI: 10.5539/ijc.v2n2p250
|View full text |Cite
|
Sign up to set email alerts
|

Densities, Viscosities and Refractive Indices of n- Butanol + Allyl Chloride Mixture at 298K

Abstract: The density ρ, viscosity η, refractive index n and dielectric constant ε s of binary mixture of Allyl Chloride (AC) with n-Butanol including those of the pure liquids, were measured over the complete composition range at 298K. The experimental data is used to calculate excess molar volumes (v E ), excess permittivity (ε s E ), excess viscosity (η E ), excess refractive index, molar refraction, excess molar polarization and Dunstan's constant. The variations of these parameters with composition and the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Figure 1 shows negative deviation of excess molar volume in MEK+NB mixtures illustrates the structural contribution, of constituents occurring by appropriate geometrical fitting in this case, i.e. better interstitial spacing of solute and solvent in the system [4][5][6][7]. The molecules of MEK assist with nitrobenzene are confirmed from our study.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Figure 1 shows negative deviation of excess molar volume in MEK+NB mixtures illustrates the structural contribution, of constituents occurring by appropriate geometrical fitting in this case, i.e. better interstitial spacing of solute and solvent in the system [4][5][6][7]. The molecules of MEK assist with nitrobenzene are confirmed from our study.…”
Section: Discussionsupporting
confidence: 60%
“…This cooperation gives the decrease in molar volume of the mixture. Leading to the formation of tightly packed hydrogenbonded aggregates (between unlike molecules) [5][6][7]. Negative value also indicates that the solute acts as a structure maker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allyl chloride (AC) is a common alkylating agent and useful in the manufacture of pharmaceuticals and pesticides due to presence of C=C double bond together with chlorine atom. 9 Maharolkar et al 9 reported the decrease in dielectric constant with addition of allyl chloride in n-butanol due to decrease in effect of hydrogen bonding. Dharne et al 10,11 reported dielectric properties of allyl chloride with dimethylformide and alcohols using the TDR technique.…”
Section: Introductionmentioning
confidence: 99%
“…n D and R m are refractive index and molar refraction of mixtures respectively. The R The Bruggeman factor ( f B ) 23 is another important parameter which may be used as an indicator of solute-solvent interactions and is given by, (9) where V is volume fraction, which is a qualitative measure of volume of the solute in the mixture. The values of static dielectric constant corresponding to mixture, component A and component B are given by ε sm , ε sA and ε sB respectively.…”
mentioning
confidence: 99%